Incerteza e dívida pública prefixada no Brasil - Gaya, Paulo Roberto de Oliveira (2006)
This study analyses the bids¿ dispersion in fixed income government securities auctions issued by the National Treasury of Brazil. We try to estimate the bids¿ variance based on factors that may forecast its movement. We hope to help the security issuer by offering more data before the auction. The basic idea is to relate the market uncertainty with the primary auction of government securities. Results indicates the importance of uncertainty on the bidding decisions. It shows also the need for a liquid secondary market to the selling of long-term fixed income securities.